1991
DOI: 10.1103/revmodphys.63.375
|View full text |Cite
|
Sign up to set email alerts
|

Boson realizations of Lie algebras with applications to nuclear physics

Abstract: The concept of boson realization (or mapping) of Lie algebras appeared first in nuclear physics in 1962 as the idea of expanding bilinear forms in fermion creation and annihilation operators in Taylor series of boson operators, with the object of converting the study of nuclear vibrational motion into a problem of coupled oscillators. The physical situations of interest are quite diverse, depending, for instance, on whether excitations for fixed-or variable-particle number are being studied, on how total angul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
416
0
7

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(425 citation statements)
references
References 537 publications
(544 reference statements)
2
416
0
7
Order By: Relevance
“…This is confirmed by many successes of the IBM [95], where the boson model is postulated including certain collective modes although their exact relation to the original fermion interaction is not rigorously derived. The regular methods of boson expansion of fermion operators were introduced in nuclear physics long ago, [96] for a single-j level and [97] for a general level scheme, see the detailed review article [98]. The application of the boson picture to our problem seems promising, especially because numerous studies of the IBM with random interactions [61,62,63,64,65,75] found a similar pattern of the predominance of J = 0 ground states.…”
Section: Boson Correlationsmentioning
confidence: 99%
“…This is confirmed by many successes of the IBM [95], where the boson model is postulated including certain collective modes although their exact relation to the original fermion interaction is not rigorously derived. The regular methods of boson expansion of fermion operators were introduced in nuclear physics long ago, [96] for a single-j level and [97] for a general level scheme, see the detailed review article [98]. The application of the boson picture to our problem seems promising, especially because numerous studies of the IBM with random interactions [61,62,63,64,65,75] found a similar pattern of the predominance of J = 0 ground states.…”
Section: Boson Correlationsmentioning
confidence: 99%
“…Using the variable Z for the identity operator I, equations (6)- (7) and (11)- (16) are the brackets for the semidirect product wsp(N, R) of the symplectic algebra sp(2N, R) with the (2N+1)-dimensional Heisenberg-Weyl Lie algebra h N [7]. This type of construction for semidirect products is typical for the study of shift operator contractions and coherent state realisations of Lie algebras [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically let us consider the generalized Marumori Boson Mapping [21]. IfÔ symbolizes a Fermionic Operator acting on the fermionic Hilbert space spanned by a finite basis of states, {|n },n= 0, 1, 2, ..., N , then the operatorÔ can be exactly represented in this basis as:…”
Section: Boson Expansionsmentioning
confidence: 99%
“…So, the Marumori mapping is an exact one [21]. Note that explicit expressions for the mapped operators are obtained, by using the expression for the vacuum Boson projector [22]:…”
Section: Boson Expansionsmentioning
confidence: 99%